Diseño de estrategias de promoción de exportaciones de artesanías en plata del cantón Chordeleg hacia el mercado de Estados Unidos. - Salazar Herrera, Juan Francisco (2015)
With the course of the years, the Ecuador crafts have had a great reception worldwide already be for his designs, colors, culture between others. The crafts in silver of the canton Chordeleg do not remain behind; one exists without number of small producers dedicated to this activity who lamentably are not taken advantage to the maximum. As in the majority of sectors in Ecuador the craftsmen do not possess a managerial vision, the activity consists of one to live daily, in the one that exists a conformity as for commercializing the crafts already is freelance in limited fairs that the government offers in not very followed dates, or intermediaries' slant that in this case they tend to be the jeweler's shops; quite this problematic is generated by the scanty knowledge that they possess in topics of exterior trade, I design in jewels, Internet managing, etc. For this motive our work of investigation consists of realizing a series of strategies of promotion of exports of the above mentioned crafts in silver towards the market of The United States. An approach exists towards this country due to the great level of consumerism that it has increased in the same one, the attraction that exists on the part of the American citizenship towards the Ecuador culture, the level of migration that has existed in the last years, accessible prices established in the products, and especially for the easy revenue that exists as for exports.